Tabor: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Food reduction must be manageable to prevent food waste; once it happens, our communitywill be as good as we expected. It must be solved, especially now that there is more and moregarbage around or even in the waste disposal bins they do not throw properly. To avoidimproper segregation of garbage every time, waste disposal must be implemented by thecompany or the people assigned to prevent that kind of problem from affecting the guests,customers, or clients around them.This study shows that upcycled foods that have an auditable supply chain were commonlyimplemented, and accepting items that were only ordered will prevent excess and wastedfood. The FIFO (First in, First Out) method is also suggested to avoid waste products as wellas proper segregation. All food waste goes to the general waste bin under two processes to gothrough, and it should also help the environment.Students should continue to be inspired and motivated to become analytic in providing theirviews on relevant and critical issues that may contribute to their field of undertaking.Employees need to gain more knowledge and be educated to avoid food waste reduction.Customers should also know and be motivated to reduce food waste when it comes toordering food.
Keywords: Business